Economic Growth and its Influence on Fatal Occupational Accidents in Peru - Gutiérrez Falcón, Pablo César (2024)
This study aims to determine how economic growth influenced fatal occupational accidents in Peru from 2011 to 2019. Data from the 24 departments, grouped into 4 macro-regions, were used and an econometric analysis using panel data was applied. This analysis consisted of assessing the stationarity of the data, and through first generation unit root tests, it was determined that they are integrated of order one. Likewise, it was found that there is a cointegration relationship between the variables (long-run equilibrium) by Pedroni panel cointegration means testing. Finally, the regression coefficients were estimated using the DOLS (Dynamic Ordinary Least Squares) estimator. It was determined that economic growth has a direct proportional relationship with fatal occupational accidents; that is to say, economic boom would cause fatal occupational accidents to increase.